Translating 6 key insights from research on leadership and management in times of crisis. Issue 4 (4th June 2021) - Reyes, Denise Lucia; Bisbey, Tiffany; Day, David; Salas, Eduardo
Abstract : Background: Certain leadership behaviours are particularly helpful for healthcare teams remain effective through crisis situations, such as the Covid-19 pandemic. This paper summarizes evidence-based insights based on their importance and prevalence in the crisis leadership literature to provide recommendations that apply to medical team leaders broadly construed. We recommend that leaders adopt these behaviours in conditions of intense difficulty, uncertainty, as well as physical and psychological peril. Results: We draw from research on workplace resilience, as well as leadership literature (ie, team leadership, transformational leadership, shared leadership, and crisis leadership) to provide six key insights along with evidence and practical guidance for healthcare leaders to help their teams in the midst of a crisis: (1) remain optimistic when communicating a vision, (2) adapt to the changing situation by deferring to team members' expertise, (3) support organizational resilience by providing relational resources, (4) be present to signal commitment, (5) be empathetic to help prevent burnout, and (6) be transparent in order to remain trustworthy.